Prevalence and correlates of asthma among 12-14 year old school children in a district and their quality life - Danansuriya, M.N (My University, 2009)
Asthma has been identified as a leading cause of functional impairment especially among children and adolescents despite major therapeutic advancements. The magnitude of prevalence and cost of the disease have made asthma a priority concern among public health authorities across the world. Adolescents with asthma suffer not only due to the chronic and intermittent nature of the illness and but also by its management strategies. Research on asthma among adolescents is necessary to monitor disease trends, to identify factors associated with it. It is also important to evaluate how asthma affects the quality of life. The present study was carried out to determine the prevalence and correlates of asthma among 12- 14 year old school children and also to assess the impact of asthma on their quality of life (QOL). The study had two components; translation and validation of instruments on general and asthma specific quality of life and a cross sectional study to determine the prevalence and correlates of asthma. A case control design was used to assess the correlates of asthma and the association of asthma and atopy was examined using skin prick testing. The prevalence study was carried out among 1483 school children of 12-14 year age group in the district of Gampaha. A stratified multistage cluster sampling method was applied in selecting the study population. A self administered questionnaire was used to collect data on prevalence and QOL. Questions on asthma screening were adopted from the ISAAC tool and the QOL was assessed using the validated Peds QL tools. One hundred and fifty eight students, identified as having current asthma were enrolled for the case control study with two healthy controls per case from the same class